2020
DOI: 10.1186/s13075-020-02154-7
|View full text |Cite
|
Sign up to set email alerts
|

Iguratimod as an alternative induction therapy for refractory lupus nephritis: a preliminary investigational study

Abstract: Objectives: Iguratimod, a novel immunomodulatory agent for rheumatoid arthritis, has been shown to be effective against murine lupus. The aim of this study was to make a preliminary evaluation of the efficacy and safety of iguratimod as salvage therapy in patients with refractory lupus nephritis (LN). Methods: We enrolled eligible patients with refractory LN, which we defined as having failed or relapsed on at least two immunosuppressant agents. After enrollment, we substituted iguratimod (25 mg twice daily) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In the first 24 weeks of the trial, IGU is compared with cyclophosphamide as an induction therapy, and in the second 24 weeks, IGU is compared with azathioprine as a maintenance therapy. In the previous observatory LN study, over 90% refractory LN patients responded to iguratimod monotherapy without any steroids increasing in the first 24 weeks of treatment [ 18 ]. Given to this outstanding effectiveness of IGU, the result of this study is expectable and promising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first 24 weeks of the trial, IGU is compared with cyclophosphamide as an induction therapy, and in the second 24 weeks, IGU is compared with azathioprine as a maintenance therapy. In the previous observatory LN study, over 90% refractory LN patients responded to iguratimod monotherapy without any steroids increasing in the first 24 weeks of treatment [ 18 ]. Given to this outstanding effectiveness of IGU, the result of this study is expectable and promising.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical study on lupus, iguratimod prevented autoimmune nephritis in MRL/lpr mice, decreased the amount of proteinuria, and reduced immune complex deposition [ 17 ]. Beyond expectation in a recent observational study, over 90% of thirteen refractory LN patients responded to iguratimod monotherapy in 24 weeks, with no steroids dose increasing or any other medication add-on during the entire follow-up [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its modulatory effect is through B cell differentiation. In an open-label study [ 48 ], 14 refractory lupus nephritis patients, 10 of whom had recent treatment failure and four had repeated relapses with inadequate initial responses, were enrolled. Out of 12 patients, five had a complete and seven a partial renal response, of whom three had a relapse within 144 weeks of follow-up.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…It suppresses antibody production by directly inhibiting the NF-κB pathway in B cells ( 7 , 8 ). Studies have highlighted its protective effects on lupus nephropathy in a mouse model and a small clinical study ( 9 , 10 ), and a recent randomized clinical trial also showed its efficacy against primary Sjögren’s syndrome ( 11 ). In a previous study, we found that IGU mitigated antibody-mediated rejection (ABMR) in a pre-sensitized mouse transplant model (unpublished), which is not surprising given the similarities between autoimmune diseases and graft rejection.…”
Section: Introductionmentioning
confidence: 99%